Arduino based outing and attendance system for boarding school students - Matthew Khoo Kah Wen; Nabihah binti Ahmad; Siti Hawa binti Ruslan (Institute of Advanced Engineering and Science, 2020)
The continuous flourishing of boarding schools in Malaysia have prompted a need for the development of outing systems that can manage the outing activities of students whilst ensuring their safety and security. In this project, a smart outing and attendance system that accurately records the details of all students and their respective outing activities is proposed. The development of this system via the XAMPP platform allows the information regarding students’ outing activities to be saved in an online database, whereby it is closely monitored and managed by the school authorities. Students who attend authorized outing activities have to scan their student ID card at an RFID reader which is installed at the main entrance of the school compound, where the information regarding their departure and arrival time at the school will be transmitted via an Arduino controller to the database. At the same time, this system sends a notification in the form of a WhatsApp message to the phone number of all the students’ parents. The system is a well-rounded approach to adequately manage the outing activities of students as each activity has to be registered beforehand with its implementation undergoing strict monitoring by the school authorities.